2016
DOI: 10.1158/1538-7445.sabcs15-p5-14-04
|View full text |Cite
|
Sign up to set email alerts
|

Abstract P5-14-04: A phase 2 study evaluating orteronel, an inhibitor of androgen biosynthesis, in patients with androgen receptor (AR)-expressing metastatic breast cancer: Interim analysis

Abstract: Background: The frequency of AR expression varies in the different breast cancer subtypes with 88%, 59%, and 32% expression reported in ER+, HER2+, and triple negative tumors, respectively. AR expression is associated with resistance to endocrine therapy in ER+ breast cancer. Androgen levels frequently increase following treatment with aromatase inhibitors suggesting a role for androgen synthesis inhibitors in ER+ breast cancer. AR signaling and expression are seen in triple negative breast cancer (TNBC), and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Clinical trials report a median progression-free survival of 12 weeks with the non-steroidal AR antagonists bicalutamide (13) and orteronel (14), but even complete responses have been observed (15). In a combination trial of the non-steroidal AR antagonist enzalutamide with the oestrogen antagonist fulvestrant, 45% of patients still remained on treatment after 24 weeks (16).…”
Section: Discussionmentioning
confidence: 99%
“…Clinical trials report a median progression-free survival of 12 weeks with the non-steroidal AR antagonists bicalutamide (13) and orteronel (14), but even complete responses have been observed (15). In a combination trial of the non-steroidal AR antagonist enzalutamide with the oestrogen antagonist fulvestrant, 45% of patients still remained on treatment after 24 weeks (16).…”
Section: Discussionmentioning
confidence: 99%
“…In phase I studies enrolling subjects with advanced TNBC and AR>10%, seviteronel showed a 16-week CBR of 33% in 16 patients, while orteronel provided a disappointing 4.8% 6 CBR at 6 months and mPFS of 2 months in 26 patients. 77 , 78 Recently, results of the first randomized phase II trial in patients with LAR BC have been presented. Patients with advanced TNBC and at least 10% expression of AR were assigned to receive the anti-androgen darolutamide (n=61) or capecitabine (n=33).…”
Section: Therapeutic Targets: Clinical Evidencesmentioning
confidence: 99%
“…However, according to ClinicalTrials.gov (accessed on 30 August 2021), there are also multiple recently completed or ongoing clinical trials investigating drugs targeting SRs other than ER for breast cancer therapy. These studies include e.g., NCT04738292 (onapristone—PR antagonist), NCT02651844 [ 7 ], NCT05016349, NCT01138553 (mifepristone—PR antagonist), NCT04947189 (seviteronel—androgen biosynthesis inhibitor), NCT01990209 (orteronel—androgen biosynthesis inhibitor) [ 8 ], NCT03383679 (darolutamide—AR antagonist), NCT00637897 (paricalcitol—vitamin D analog) [ 9 ] or NCT01708798 (eplerenone—MR antagonist; for cardiotoxicity prevention) [ 10 ]. Most likely, in the near future further drugs targeting these receptors will be tested.…”
Section: Introductionmentioning
confidence: 99%